2021
DOI: 10.1161/circinterventions.121.010698
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Pancoronary Quantitative Flow Ratio Assessment in Patients Undergoing Percutaneous Coronary Intervention for Acute Coronary Syndromes

Abstract: Background: Quantitative flow ratio (QFR) has been introduced as a novel angiography-based modality for fast hemodynamic assessment of coronary artery lesions and validated against fractional flow reserve. This study sought to define the prognostic role of pancoronary QFR assessment in patients with acute coronary syndrome (ACS) including postinterventional culprit and nonculprit vessels. Methods: In a total of 792 patients with ACS (48.6% ST-segment–el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…More recently, new modalities, such as iFR and QFR, have been investigated to provide additional data about the importance of post-PCI coronary physiology in relation to long-term outcomes. [16][17][18][19]22,23 The current meta-analysis pooled the data of the currently available studies on the value of post-PCI physiological assessment using FFR, iFR, and QFR. This is the first meta-analysis providing data about several physiological assessment modalities, including iFR and QFR.…”
Section: Post-pci Physiologymentioning
confidence: 99%
“…More recently, new modalities, such as iFR and QFR, have been investigated to provide additional data about the importance of post-PCI coronary physiology in relation to long-term outcomes. [16][17][18][19]22,23 The current meta-analysis pooled the data of the currently available studies on the value of post-PCI physiological assessment using FFR, iFR, and QFR. This is the first meta-analysis providing data about several physiological assessment modalities, including iFR and QFR.…”
Section: Post-pci Physiologymentioning
confidence: 99%
“…The recently published studies focusing on the prognostic value of QFR in patients with ACS are presented in Table 4 (16,17,32,(50)(51)(52)(53)(54)(55)(56)(57). A study by Choi et al (32) enrolling 452 all-comer patients with CAD (25.9% with ACS) demonstrated that vessels with QFR≤0.80 showed a significantly higher risk of vessel-related adverse events Another important clinical scenario to perform physiological assessment is in the catheterization laboratory after the index procedure.…”
Section: Prognostic Value Of Qfr Measurement In Acsmentioning
confidence: 99%
“…The recently published studies focusing on the prognostic value of QFR in patients with ACS are presented in Table 4 ( 16 , 17 , 32 , 50 - 57 ). A study by Choi et al ( 32 ) enrolling 452 all-comer patients with CAD (25.9% with ACS) demonstrated that vessels with QFR ≤0.80 showed a significantly higher risk of vessel-related adverse events compared to those with QFR >0.80 at 2-year [hazard ratio (HR) 4.650, 95% CI: 1.254–17.240, P=0.022].…”
Section: Prognostic Implications Of Qfr In Acsmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiological assessment after PCI, such as quantitative flow ratio (QFR) analysis, can be used as an effective means to quantify residual coronary ischemia (4)(5)(6). Studies have confirmed that poor post-PCI QFR is associated with a poorer prognosis, but the susceptibility factors affecting poor postoperative QFR remain unclear (7)(8)(9). Therefore, identifying risk factors for poor postoperative QFR has important clinical significance for reducing the risk of coronary residual ischemia.…”
Section: Introductionmentioning
confidence: 99%